The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1590/s0104-66322003000200004
|View full text |Cite
|
Sign up to set email alerts
|

Improving heat transfer in stirred tanks cooled by helical coils

Abstract: Stirred Tank Reactors are extensively used in chemical industries. When they are used for highly exothermic reactions, jackets or coils are employed for heat removal. Internal coils can be either helical or axial and they considerably affect the flow inside the reactor because they impose an additional resistance to flow circulation. The aim of this work is to show that the design of vessels cooled by helical coils can be further improved. The design of these reactors follows very much the geometry proposed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…This approach overcomes the assumption of perfect mixing, which is a major flaw of lumped‐parameter models. In previous CFD based modelling studies of heat transfer, for example, in baffled STRs and unbaffled STRs, the simulation of temperature distributions in the vessel was carried out using a prescribed uniform thermal boundary condition at the inner surface of the vessel wall such as the wall temperature and heat transfer coefficient. Yapici and Basturk carried out semi‐conjugate (coupled process and wall) heat transfer simulations in an unbaffled hemispherical agitated vessel, not representative of industrial STRs, using the temperature and heat transfer coefficient as boundary conditions at the outer surface of the vessel wall.…”
Section: Introductionmentioning
confidence: 99%
“…This approach overcomes the assumption of perfect mixing, which is a major flaw of lumped‐parameter models. In previous CFD based modelling studies of heat transfer, for example, in baffled STRs and unbaffled STRs, the simulation of temperature distributions in the vessel was carried out using a prescribed uniform thermal boundary condition at the inner surface of the vessel wall such as the wall temperature and heat transfer coefficient. Yapici and Basturk carried out semi‐conjugate (coupled process and wall) heat transfer simulations in an unbaffled hemispherical agitated vessel, not representative of industrial STRs, using the temperature and heat transfer coefficient as boundary conditions at the outer surface of the vessel wall.…”
Section: Introductionmentioning
confidence: 99%
“…One can design the new equipment and also carry out the trouble shooting of any chemical process using CFD. There were several studies reported on CFD modeling agitated vessel to find out flow modeling and mixing performance. Several studies also reported on modeling of heat transfer studies using nanofluids in agitated vessel .…”
Section: Introductionmentioning
confidence: 99%
“…Their study also includes the effects of the types of the agitators and their configuration on heat transfer process. Pedrosa and Nunhez (2003) showed that the design of vessels cooled by helical coils can be further improved by introducing some minor modifications in the coil arrangements. Triveni et al (2008) studied heat transfer of few industrially important systems namely castor oil and its methyl esters, soap solution, CMC and chalk slurries in a stirred vessel fitted with anchor/turbine impeller and a coil for heating or cooling.…”
Section: Introductionmentioning
confidence: 99%